Impact of Lifetime Alcohol Use on Liver Fibrosis in a Population of HIV‐Infected Patients With and Without Hepatitis C Coinfection. (3rd May 2013) - Fuster, Daniel; Tsui, Judith I.; Cheng, Debbie M.; Quinn, Emily K.; Bridden, Carly; Nunes, David; Libman, Howard; Saitz, Richard; Samet, Jeffrey H.
Abstract : Background: The effect of alcohol on liver disease in HIV infection has not been well characterized. Methods: We performed a cross‐sectional multivariable analysis of the association between lifetime alcohol use and liver fibrosis in a longitudinal cohort of HIV‐infected patients with alcohol problems. Liver fibrosis was estimated with 2 noninvasive indices, "FIB‐4, " which includes platelets, liver enzymes, and age; and aspartate aminotransferase/platelet ratio index ("APRI"), which includes platelets and liver enzymes. FIB‐4 <1.45 and APRI <0.5 defined the absence of liver fibrosis. FIB‐4 >3.25 and APRI >1.5 defined advanced liver fibrosis. The main independent variable was lifetime alcohol consumption (<150 kg, 150 to 600 kg, >600 kg). Results: Subjects ( n  = 308) were 73% men, mean age 43 years, 49% with hepatitis C virus (HCV) infection, 60% on antiretroviral therapy, 49% with an HIV RNA load <1, 000 copies/ml, and 18.7% with a CD4 count <200 cells/mm 3 . Forty‐five percent had lifetime alcohol consumption >600 kg, 32.7% 150 to 600 kg, and 22.3% <150 kg; 33% had current heavy alcohol use, and 69% had >9 years of heavy episodic drinking. Sixty‐one percent had absence of liver fibrosis and 10% had advanced liver fibrosis based on FIB‐4. In logistic regression analyses, controlling for age, gender, HCV infection, and CD4 count, no association was detected between lifetime alcohol consumption and the absence of liver fibrosis (FIB‐4 <1.45) (adjusted odds ratio [AOR] = 1.12 [95% CI: 0.25 to 2.52] for 150 to 600 kg vs. <150 kg; AOR = 1.11 [95% CI: 0.52 to 2.36] for >600 kg vs. <150 kg; global p  = 0.95). Additionally, no association was detected between lifetime alcohol use and advanced liver fibrosis (FIB‐4 >3.25). Results were similar using APRI, and among those with and without HCV infection. Conclusions: In this cohort of HIV‐infected patients with alcohol problems, we found no significant association between lifetime alcohol consumption and the absence of liver fibrosis or the presence of advanced liver fibrosis, suggesting that alcohol may be less important than other known factors that promote liver fibrosis in this population.